The importance of the example parents set in regards of sport and childhood activities related to physical exercise (Training and Practice : Journal of Educational Sciences, 2020)
I consider that parents have a high responsibility in forming a child’s attitude towards sports and physical exercise essential to health promotion, as they shape their child’s need for exercise and influence the preservation of the child’s health by setting a good example. In my research I focus on the influence of the parents’ example when establishing their pre-school child’s routine related to sports. As a conclusion, based on my research, we can say without bias that those children are more likely to do sports regularly, whose parents do regular exercise themselves ever since they were children. On the other hand, those children are less likely to start sporting activities, whose parents do not do physical exercise regularly or did not do sports when they were children.